Emerging Market Securities Access to Global Plumbing - Choi, Gongpil (IMF Working Papers; Working Paper, 2021)
What are the constraints that have stalled EMs efforts to reuse their securities in international financial centers? We discuss the economics of collateral re-use and the present institutional structure in Asian and Latin American countries. Our empirical investigation suggests pledgeability enhances financial stability and reduces dollar funding risk. We also explain the Eurozone collateral pool to incentivize EMs, and why many securities (e.g., BTPs, Italy) are acceptable in London but not EM securities. Looking forward, EMs liaison with International Central Securities Depositories (ICSDs), and global banks' balance sheet capacity to intermediate cross-border collateral will be crucial for this market to develop.